The sawfly genus Phymatocera (Hymenoptera: Tenthredinidae) of Japan - Hara, Hideho; Ibuki, Shinichi; Vårdal, Hege (Zootaxa, 2025)
Generic characters of Phymatocera Dahlbom, 1835 are detailed. The following five Japanese species of Phymatocera are described or redescribed and divided into two species groups: Species group of P. aterrima: P. membra Wei, 2002 from Japan (Kyushu) and China (Henan), P. nipponica Togashi, 1958 from Japan (Shikotan Island, Rishiri Island, Hokkaido, Honshu, Shikoku, Kyushu, Tsushima Island), Korea and Russia (Sakhalin), and P. satoi Hara, sp. nov. from Japan (Honshu); Species group of P. fumipennis: P. fuscata (Togashi, 1984) comb. nov. (= Rhadinoceraea fuscata Togashi, 1984) from Japan (Honshu), and P. peregrinator (Malaise, 1931) comb. nov. (= Neotomostethus peregrinator Malaise, 1931) from Japan (Hokkaido, Honshu) and Russia (Kamchatka). A key to these five Japanese species is given. Phymatocera hokkaidonis Togashi, 2004 syn. nov. is synonymized with N. peregrinator. A lectotype is designated for Neotomostethus peregrinator Malaise, 1931. New distributional records are P. membra from Honshu, Japan, P. nipponica from Rishiri Island and Tsushima Island, Japan, and P. peregrinator comb. nov. from Honshu, Japan. The genus Rhadinoceraea Konow, 1886 is excluded from the fauna of Japan, because the only known Japanese species of the genus, R. fuscata, is transferred to Phymatocera. The following new combinations are proposed for two Chinese species: Rhadinoceraea foveata (Wei, 1998) comb. nov. (= Phymatocera foveata Wei, 1998, in Nie & Wei 1998) and Rhadinoceraea sinica (Wei, 2002) comb. nov. (= Phymatocera sinica Wei, 2002).